Transformasi Pendidikan Sepanjang Hayat Sebagai Strategi Adaptif dalam Dinamika Dunia Abad 21 - Farah Qotrun Nada; Abdul Khobir; Elia Nur Rohmah; M. Khafidz Alfaza; Untung Arif Warasanto (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Social, technological, and global economic transformations in the twenty-first century necessitate a fundamental shift in education from a linear model toward a lifelong and continuous learning orientation. Lifelong education is increasingly recognized as an adaptive strategy to enhance individual and societal readiness in responding to a world characterized by growing complexity and uncertainty. This study aims to examine the role of lifelong education within the framework of twenty-first-century education by emphasizing learning paradigms, the roles of educators and curricula, as well as the integration of technology and social adaptation. The research employs a qualitative approach through a literature-based study of academic books and peer-reviewed journal articles relevant to twenty-first-century education and lifelong learning. The findings indicate that lifelong education contributes significantly to the strengthening of competencies, digital literacy, soft skills, and character development, while fostering an adaptive learning culture. This transformation reaffirms education as a strategic, life-long process in the development of globally competitive human resources.